2017
DOI: 10.1093/neuros/nyx052
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory and Th17 Immune Activation among Patients Treated for Lumbar Radiculopathy Exceeds that of Patients Treated for Persistent Postoperative Neuropathic Pain

Abstract: Differences in Th17 immune activation are seen among radiculopathy and neuropathic pain patients. These cellular and molecular profiles may be translated into biomarkers to improve patient selection for structural spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Accordingly, pain intensity was positively correlated with increased levels of Th17-cells and IL-17 expression. These research findings lead to the assumption that IL-17-producing T-helper cells trigger an inflammatory reaction and are responsible for the development and maintenance of pain [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, pain intensity was positively correlated with increased levels of Th17-cells and IL-17 expression. These research findings lead to the assumption that IL-17-producing T-helper cells trigger an inflammatory reaction and are responsible for the development and maintenance of pain [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition to repair cells that deposit granulation tissue, immune cells such as pro-inflammatory macrophages, T lymphocytes, and mast cells have been implicated in poor adult AF healing. 24,4851 However, mechanistic studies testing the requirement of these cells in healing have not been carried out and the sources of fibrotic repair cells remain largely unidentified. Fibronectin is a fibrotic marker associated with IVD degeneration and has been previously identified via immunostaining in degenerated human IVD tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found TNF-α was up-regulated in local nucleus cells and peripheral blood [ 28 , 39 ]. This finding is in line with previous studies.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, evidence showed that TNF-α is the base of inflammation in IDD process [ 26 ]. Clinical study showed that the level of TNF-α was related to low back pain in patients [ 4 , 27 , 28 ]. Higher TNF-α level indicated suffering more pain.…”
Section: Discussionmentioning
confidence: 99%